2020
DOI: 10.1111/ajgw.12469
|View full text |Cite
|
Sign up to set email alerts
|

Effect of grape heterogeneity on wine chemical composition and sensory attributes forVitis viniferacv. Cabernet Sauvignon

Abstract: Background and Aims: The wine industry widely acknowledges that grape heterogeneity exists throughout any given vineyard at the time of harvest. There is a lack of understanding, however, of the effects that heterogeneity has on wine composition and sensory qualities. This study compared the chemical composition and sensory attributes of wines produced using parcels of grapes with known heterogeneity. Methods and Results: Cabernet Sauvignon berries were sorted into maturity classes using five density baths. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…SPME–GC–MS was performed with an Agilent 7890B gas chromatograph (Santa Clara, CA) fitted with an Agilent GC Injector 80 and coupled to an Agilent 7000C triple-quadrupole mass spectrometer. SPME and chromatographic conditions were reported in Armstrong et al with a slight modification to the injector temperature (set to 250 °C). For multiple-reaction monitoring, transitions were as reported by Armstrong et al with the addition of m / z 151.0 → 123.0, 151.0 → 119, and 124.0 → 94.0 for SBMP; 154.0 → 126.0 and 127.0 → 95.0 for d 3 -SBMP (internal standard); and 155.0 → 127.0, 140.0 → 105.0, 127.0 → 95.0, and 155.0 → 140.0 for d 3 -IPMP (internal standard).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SPME–GC–MS was performed with an Agilent 7890B gas chromatograph (Santa Clara, CA) fitted with an Agilent GC Injector 80 and coupled to an Agilent 7000C triple-quadrupole mass spectrometer. SPME and chromatographic conditions were reported in Armstrong et al with a slight modification to the injector temperature (set to 250 °C). For multiple-reaction monitoring, transitions were as reported by Armstrong et al with the addition of m / z 151.0 → 123.0, 151.0 → 119, and 124.0 → 94.0 for SBMP; 154.0 → 126.0 and 127.0 → 95.0 for d 3 -SBMP (internal standard); and 155.0 → 127.0, 140.0 → 105.0, 127.0 → 95.0, and 155.0 → 140.0 for d 3 -IPMP (internal standard).…”
Section: Methodsmentioning
confidence: 99%
“…SPME and chromatographic conditions were reported in Armstrong et al with a slight modification to the injector temperature (set to 250 °C). For multiple-reaction monitoring, transitions were as reported by Armstrong et al with the addition of m / z 151.0 → 123.0, 151.0 → 119, and 124.0 → 94.0 for SBMP; 154.0 → 126.0 and 127.0 → 95.0 for d 3 -SBMP (internal standard); and 155.0 → 127.0, 140.0 → 105.0, 127.0 → 95.0, and 155.0 → 140.0 for d 3 -IPMP (internal standard). Underlined transitions were used for quantification and all transitions were monitored with a 50 ms dwell time.…”
Section: Methodsmentioning
confidence: 99%
“…The predominant grape methoxypyrazine, 3-isobutyl-2-methoxypyrazine (IBMP), was quantified in frozen, powdered Cabernet Sauvignon grape berry tissue, as described by Armstrong et al (2021); rotundone was quantified in the equivalent Shiraz samples following the method of Davies et al (2015).…”
Section: Quantification Of Methoxypyrazines and Rotundone In Grape Ti...mentioning
confidence: 99%
“…The phenomenon of NAA treatment altering the synchronicity of the ripening of the grape berry population, observed previously (Böttcher et al 2011b(Böttcher et al , 2012, may mean that the metabolism of these berries is better synchronised in these populations. Armstrong et al (2021) sorted a berry population into different classes on the basis of density and showed that the level of heterogeneity had demonstrable effects on wine composition and sensory characteristics. While some variation in berry developmental stage might be useful in providing complexity to wine, too much heterogeneity may reduce consumer acceptance.…”
Section: Naa Treatment Altered the Synchronicity Of Berry Mass And Ts...mentioning
confidence: 99%